Does the distance between the nest and the food source affect the foraging behavior of Nasutitermes corniger (Termitidae)? - Souza, Thiago Sampaio de (2023)
Research on food finding by pest termites can be used to inform the development of techniques to control their population; however, there is a paucity of information available on the foraging behavior of Nasutitermes corniger, an urban pest in South America. In the present study, we analyzed the effect of the distance between the nest and food on the exploration and recruitment of N. corniger during foraging behavior under laboratory conditions. Nests containing mature colonies were collected in the field and placed in a glass cube connected to a test arena (50.0 × 40.0 cm) in which Eucalyptus grandis blocks were supplied at three different distances: 10, 20 and 30 cm. In each test, the occurrence of the following events were recorded: initial exploitation, initial recruitment, and mass worker recruitment. Individuals in the blocks were counted at the end of each test and divided into the total number of recruited termites, recruited workers, consuming workers and recruited soldiers. Each test lasted 60 minutes and was repeated with 20 colonies. Nasutitermes corniger foragers showed the three behavioral events of interest at all three distances. The occurrences of initial exploitation and initial recruitment, the latency of the three events and the number of foragers were not affected by the distance between the nest and food. The occurrence of mass worker recruitment was the only event affected by this distance, with higher recruitment at shorter distances.